THE EFFECTIVENESS OF STORY COMPLETION ON THE EIGHTH GRADE STUDENTS OF SPEAKING SKILLS OF SMPI SALAFIYAH SINGOSARI IN THE ACADEMIC YEAR 2021/2022 - Maulana Fahmi Idris (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2022)
Fahmi Idris. Maulana 2022. The effectiveness between using story completion technique and role play on the eighth grade students speaking skills of smpi salafiyah singosari in the academic year of 2021/2022. Skripsi, English Education Department Faculty of Teacher Training and Education University of Islam Malang. Advisor I: Dr.Dra.Hj.Mutmainnah ,M.pd.; Advisor II: Dr. Imam Wahyudi Karimuallah, S. S, M. Pd. The study aims to investigate the effectiveness of story completion techniques in developing speaking skills and overcoming lack of confidence at the eighth grade students of SMPI SALAFIYAH SINGOSARI. The researcher optimized the experimental research designs that used pre-test and post-test with quantitative approaches. The researcher took all eighth students as population. The researcher used probability purposive sampling in determining the sample with 28 students from class 8 as experimental and control group. The independent variable is story completion technique and the dependent variable is students' speaking skills. The researcher compares pre-test and posttest results between two groups from inter-rater and used an independent SPSS t-test to analyze the data. The pre-test to posttest of experimental was 48.25 to 65.50, control group was 46.63 to 57.13, and the p-value was 0.033, p= < 0.05. As a result, the researcher concluded that there was significant effect of using story completion on students’ speaking skill.  Keywords: effective, story completion technique, studeny speaking skill.